Rondallas of Cainta a historical overview from the 1950s to early 2000 - Opiso, Roan May De Guzman
This paper aims to provide a preliminary documentation of the history of the rondalla groups in the municipality of Cainta, Rizal. It aims to discuss how they were formed, sustained and changed while noting the various socio-political aspects such as the patronage system that contributed in shaping the musical tradition. Tha main focus of the paper is the history of rondalla groups in a local community, with the development of national rondalla tradition a the background.